1988
DOI: 10.1007/bf00177574
|View full text |Cite
|
Sign up to set email alerts
|

?First-dose? response to mianserin: effects of age

Abstract: The effects of single 10 mg oral doses of the antidepressant mianserin on psychomotor performance, subjective sedation and supine and standing blood pressure were compared in ten young and nine elderly healthy volunteers. Immediate and residual sedation following this subtherapeutic dose was readily detected in both groups. In contrast to previous studies with benzodiazepines, the sedation effect was not accentuated in the older subjects. Subjective awareness of sedation was significant in the young but not, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Sedative drugs such as pentobarbital, chlorpromazine, diazepam, mianserin, and nitrous oxide produce impairments in attention-related tasks, whereas stimulants such as caffeine and amphetamine lead to improvements (Clubley, Bye, Henson, Peck, & Riddington, 1979;Fagan, Paul, Drummond, Scott, & Tiplady, 1989;Fagan, C. G. Swift, & Tiplady, 1988;Hart, Hill, Bye, Wilkinson, & Peck, 1976;Mackworth, 1965;Mirsky & Kornetsky, 1964;C. G. Swift, M. R. Swift, & Tiplady, 1988).…”
mentioning
confidence: 99%
“…Sedative drugs such as pentobarbital, chlorpromazine, diazepam, mianserin, and nitrous oxide produce impairments in attention-related tasks, whereas stimulants such as caffeine and amphetamine lead to improvements (Clubley, Bye, Henson, Peck, & Riddington, 1979;Fagan, Paul, Drummond, Scott, & Tiplady, 1989;Fagan, C. G. Swift, & Tiplady, 1988;Hart, Hill, Bye, Wilkinson, & Peck, 1976;Mackworth, 1965;Mirsky & Kornetsky, 1964;C. G. Swift, M. R. Swift, & Tiplady, 1988).…”
mentioning
confidence: 99%
“…The sensitivity and validity of the tests in the APT battery (e.g. CAT, CRT and CFFT) has been established during acute drug studies in elderly people [18][19][20][21][22][23]. However, the repeatability of these tests in elderly people, which may be important in assessing the psychomotor effects of long-term drug therapy, has not been previously assessed.…”
Section: Introductionmentioning
confidence: 99%
“…These results highlight reports that some patmnts experience fainting when treatment with tricyclic antidepressants is initiated. Swift, Swift and Tiplady (1988) have also investigated a single dose of mianserin (10 mg) in ten young volunteers (aged 19-37 years) and nine elderly volunteers (aged 67-76 years). The authors concluded that the sedative properties of mianserin were observed to the same extent in both the young and elderly groups.…”
mentioning
confidence: 99%
“…No clinically significant abnormalities were seen on the volunteers" screening ECGs or those taken at peak hypotensive effect. Swift et al (1988) postulated that as they had not observed a first dose hypotensive effect of mianserin in the elderly, this may be due to the loss of responsiveness of the post-synaptic cc-2 receptor which occurs with ageing (Hyland and Docherty 1985). Indeed, this may be responsiOffprint requests to: A.K.…”
mentioning
confidence: 99%
See 1 more Smart Citation